Government’s Role in Enhancing Economic InclusionThrough Digital Infrastructure Equity in Indonesia - Himmati, Risdiana; Dana, Badara Shofi; Wati, Aprilia Eka Fajar (Signifikan: Jurnal Ilmu Ekonomi, 2025)
Research Originality: This research is original in its examination of the equitable distribution of digital infrastructure in enhancing economic inclusion in Indonesia, employing a fixed effect model and quantile regression approach. Research Objectives: This study investigates the impact of the equitable distribution of digital infrastructure on enhancing economic inclusion in Indonesia. Research Methods: This study employs a fixed effect model and quantile regression, analyzing data from 34 provinces between 2019 and 2023. Key variables include internet access, internet speed, the number of Base Transceiver Stations (BTS), and digital literacy. Empirical Results: The findings reveal that internet access and internet speed have a positive and significant impact on digital financial inclusion, whereas the number of BTS and digital literacy exhibit no significant effect. The impact of digital infrastructure varies across regions, with areas exhibiting lower financial inclusion requiring greater infrastructure optimization compared to those with higher inclusion levels. Implications: The results imply that digital infrastructure development plays a critical role in promoting equitable financial inclusion. Consequently, policymakers are urged to prioritize and accelerate the expansion of digital infrastructure, particularly in regions lagging behind, to reduce financial exclusion and foster inclusive economic development at the national level. JEL Classification: O33, O10, G28, C23, C21 How to cite: Himmati, R., Dana, B. S., & Wati, A. E. F. (2025). Government’s Role in Enhancing Economic Inclusion Through Digital Infrastructure Equity in Indonesia. Signifikan: Jurnal Ilmu Ekonomi, 14(2), 291-302. https://doi.org/10.15408/sjie.v14i2.45574.